Sleep behaviors and nutritional knowledge in amateur and professional combat sport athletes - Dunican, I. C.; Galpin, A.; Turner, M.; Reale, R. (The Journal of Strength and Conditioning Research, 2024)
Combat sports is a term applied to various competitive contact sports involving 2 competitors engaging in a bout or contest under a specific ruleset. Little is known about combat sports athletes' sleep and nutritional knowledge. This study aimed to assess (a) sleep behaviors, (b) alcohol and shiftwork disorders, and (c) the nutritional knowledge of combat sports athletes. Subjects completed various demographic questions and estimations of their weight management practices and validated surveys, including the Athlete Sleep Behavior Questionnaire, Shiftwork Disorder (SWD) Screening Questionnaire, Alcohol Use Disorders Identification Test, and the Abridged Nutrition for Sports Knowledge Questionnaire. A total of 844 combat sports athletes completed the survey, 79% male, height of 177 ± 10 (cm), and body mass of 79 ± 15 (kg). Subjects were categorized into their specific combat sport type (e.g., boxing or Brazilian jiu-jitsu [BJJ]) and by their level (professional or amateur). Sleep quality was average for all combat sport types and risk prevalence of shiftwork disorder at 11%. Mann-Whitney U tests revealed that amateurs, compared with professional strikers (p = 0.046, CLES = 0.80), boxers (p = 0.01, CLES = 0.78), and BJJ (p = 0.046, CLES = 0.61) athletes, consumed significantly more alcohol. A Friedman test showed significant (p < 0.001, W = 0.51) differences in weight between time points, with most combat sports athletes reducing weight for competition. An overall nutritional knowledge average of 55% was reported. This study highlights a critical gap in the knowledge and practices of combat sports athletes in relation to sleep behaviors and disorders, alcohol consumption, and nutritional knowledge, emphasizing the need for targeted educational interventions.